A Participatory Evacuation Map Making Towards Sustainable Urban Heritage Kotagede, Yogyakarta - Dyah R Hizbaron; Sudibyakto Sudibyakto; Raditya Jati; Hidehiko Kanegae; Yusuke Toyoda (Forum Geografi, 2015)
This research aims at development of Participatory Evacuation Map Making (PEMM) for Kotagede, Yogyakarta – Indonesia. The research area is one of an important cultural heritage sites in Indonesia which is subjected towards earthquake hazard. The preliminary observation revealed that the area is a densely populated area, which characterized by dense wooden building structure, narrow street and minimum information of evacuation route which increase their vulnerability potentials. This leads to the idea of developing the PEMM to improve their awareness and preparedness during disaster events and creates sustainable condition for local livelihood security. The method develops within this research is actually a lesson learn from Ritsumeikan University, that has developed CSR for integration disaster management into heritage sites at Kyoto Prefecture. Their CSR covers several activities such as developing disaster information via vending machine and tourism map. Since Yogyakarta and Kyoto are engaged in “Sister City Development Program”, hereafter Universitas Gadjah Mada tries to do similar thing. Map making is an alternative prior to community experience in map making is rather frequent compare to vending machine habit. The preliminary finding of this research indicates that the Kotagede community has been involved in several map making activity, such as “Green Map” and “Rehabilitation Sites Map”.  However, they have not yet any experience to create any map which includes information such as evacuation route, fire extinguisher, shelter information center and important meeting points. An improved critics from this research is to include meeting points level. As we all aware off, each meeting point have significant carrying capacity, thereby in the future a research on similar topics should add level and or category of meeting points. This is an important steppingstone for the research to conduct further research.